Vancomycin-Resistant E. faecium: Addressing Global and Clinical Challenges - Daniel E. Radford-Smith; Daniel C. Anthony (Antibiotics)
Antimicrobial resistance (AMR) poses a profound threat to modern healthcare, with vancomycin-resistant Enterococcus faecium (VREfm) emerging as a particularly resilient and clinically significant pathogen. This mini-review examines the biological mechanisms underpinning VREfm resistance, including biofilm formation, stress tolerance, and the acquisition of resistance genes such as vanA and vanB. It also explores the behavioural, social, and healthcare system factors that facilitate VREfm transmission, highlighting disparities in burden across vulnerable populations and low-resource settings. Prevention strategies are mapped across the disease pathway, spanning primary, secondary, and tertiary levels, with a particular focus on the role and evolving challenges of antimicrobial stewardship programmes (ASP). We highlight emerging threats, such as rifaximin-induced cross-resistance to daptomycin, which challenge conventional stewardship paradigms. Finally, we propose future directions to enhance global surveillance, promote equitable stewardship interventions, and accelerate the development of innovative therapies. Addressing VREfm requires a coordinated, multidisciplinary effort to safeguard the efficacy of existing antimicrobials and protect at-risk patient populations.